FACTORS THAT ENCOURAGE MELAYU PEOPLE TO FOLLOW THE SYATTARIYYAH TARIKAT OF SYEKH H. ABDURRAHMAN SILAU LAUT - Syukri Syukri; Sulaiman Muhammad Amir; Safria Andy (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
The study of Malays, is inseparable from their beliefs and concerns about the teachings of Islam. But does every Malay person want to enter the tarikat, specifically the Syattariyah Tarikat Mr. Sheikh H. Abdurrahman Silau Laut. If so, what factors drove them to enter it? Therefore, this paper focuses on in-depth interviews (dept interview), using the "filed risearch" and "frame of reference" methods. The aim is to find out the factors that drive them into this path. The results and discussion of this study, found that many Malay people entered the Syattariyah Tarikat which was founded by Mr. Sheikh H. Abdurrahman Silau Laut in Silau Laut District. There are two factors that encourage them to enter this path. First, the interinsic factor of the Malays wants to draw closer to Allah, and also wants to explore psychology. Secondly, the exinsic factor because it is motivated by others and all positive views towards the person of Mr. Sheikh of Silau Lautand the teachings of his path, karomah, i'iqad and his actions encourage them to enter this path. To the local government, scholars, pilgrims and the community paid serious attention to the preservation of the teachings of Tarikat Syattariyah as a scientific institution for the next generation. Keywords: Syattaryyah Tarikat, Abdurrahman, Silau Laut, Motivation, Melayu People of Asahan.